CONTRIBUTION OF BANJAR ULAMA IN THE DEVELOPMENT OF ISLAMIC EDUCATION IN SAMARINDA CITY - Khojir Khojir (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract:Samarinda is a multi-ethnic city, and there are various urban Ulama in Samarinda such as Javanese, Banjar, Bugis, and Madurese Ulama. Urban Ulama has made a significant contribution to the development of Islam. This research specifically examined the contribution of Banjar Ulama in the development of Islamic education. The purpose of this article was to determine the contribution of Banjar Ulama to Islamic Education in Samarinda City. This research used a qualitative study with a historical-phenomenological approach. The data sources were from Banjar figures, Paguyuban Banjar, and Banjar Ulama and data collection procedures were done through in-depth interviews and documentation. Data were analyzed using qualitative analysis, namely data reduction, presentation and concluding. The results showed that Banjar Ulama contributed to the development of Islamic education in Samarinda City. The contribution was 1) establishing various types of Majelis Ta’lim in various cities of Samarinda; 2) functioning the mosque as a community education centre (congregation); 3) establishing formal education in madrasah and Islamic universities; 4) founding the first Islamic boarding school in Samarinda; 5) writing books as a reference in providing material in Majelis Ta’lim and the general public. Therefore, the results of this research were the evidence that the Banjar Ulama contributed in real terms to the development of education in Samarinda City.Abstrak:Samarinda merupakan kota multi etnis dan terdapat berbagai Ulama urban di Samarinda seperti Ulama Jawa, Banjar, Bugis, Madura.  Ulama urban mempunyai kontribusi yang signifikan dalam pengembangan Islam. Penelitian ini secara khusus mengkaji kontribusi Ulama Banjar dalam pengembangan Pendidikan Islam. Tujuan penulisan artikel ini adalah untuk mengetahui kontribusi Ulama Banjar dalam Pendidikan Islam di Kota Samarinda. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan historis-fenomenologis. Sumber data digali dari para tokoh Banjar, Paguyuban Banjar, dan Ulama keturanan Banjar. Metode penggalian data yaitu wawancara mendalam dan dokumentasi. Analisis data menggunakan analisis kualitatif yaitu reduksi data, penyajian dan penarikan kesmpulan. Hasil penelitian menunjukkan bahwa Ulama Banjar berkontribusi pada pengembangan pendidikan Islam di Kota Samarinda. Bentuk kontribusinya yaitu 1) mendirikan berbagai jenis mejelis Ta’lim diberbagai kota Samarinda; 2) memfungsikan masjid sebagai pusat pendidikan masyarakat (jamaah); 3) mendirikan Pendidikan formal berupa madrasah dan perguruan tinggi Islam; 4) mendirikan pesantren pertama di Samarinda; 5) menulis kitab sebagai referensi dalam memberikan materi dalam Majelis Ta’limmaupun masyarakat umum. Dengan hasi penelitian tersebut membuktikan bahwa Ulama Banjar berkontribusi secara riil pada pengembangan Pendidikan di Kota Samarinda.